The Impact of Corporate Governance and Risk Management on Bank Performance in UK - DING, YIPEI (2022)
Risk management and corporate governance are very vital for a bank as the success or failure of the bank relies on the conclusive roles played by the two roles. This research therefore aimed at investigating the impact of corporate governance and risk management in the performance of banks in the UK. This dissertation has conducted a cross-section survey of 75 banks in the UK. Secondary data relating to the 75 banks’ corporate governance, risk management and financial performance by abstracting this information from financial and corporate governance reports of the banks as published in their financial reports and in other trusted financial databases. Data collected was entered in excel for sorting and arrangement and then entered in SPSS for analysis. Using multiple regression analysis, the impact of components of corporate governance and risk management on banks’ performance was determined. The results showed that multiple regression model had an R-Square of .784 meaning that the independent variables determine to about 78.4% of the dependent variables. The model had a low F statistic (34) and a Sig =.000<.05 and hence we conclude that the independent variables significantly predict the dependent variables. Components of corporate governance (ND, Age, ID, and AE) significantly determined the performance of banks (sig.<.05) and hence we partially accept the first null hypothesis that corporate governance significantly influences the performance of banks in the UK. All the, components of risk management significantly determined (Sig. <.05) the performance of banks in the UK and thus we accept the second null hypothesis that risk management significantly influence the performance of banks in the UK. Therefore, corporate governance and risk management significantly determines the performance of banks in the UK. Finally, this dissertation makes a recommendation to the banks to prioritize corporate governance and risk management efficiency in sustaining high performance.